Main clinical and epidemiologic characteristics of patients with hypertension in a community health area from Venezuela - Daiviel Hidalgo Alvarez; Reynaldo Rodríguez Labañino; Soini González Gámez; Justo Moises Peña Reyes; Ana Selva Capdesuñer (Centro Provincial de Información de Ciencias Médicas, 2023)
Introduction: Hypertension constitutes a health problem worldwide, due to the progressive increase of its prevalence and incidence.  Objective: To describe the main clinical and epidemiologic characteristics of patients with hypertension.  Methods: A descriptive, cross-sectional and ambispective study was carried out from April, 2020 to the same month in 2021 of 50 patients with hypertension assisted in La Morita Doctor's Office of Progreso Community Integral Health Area, Portuguese state, in the Bolivian Republic of Venezuela. In the statistical process of the information the percentage as summary measure was used. Results: In the series there was prevalence of the 80 years and over age group (26.0%), female sex (54.0%), the combined treatment (70.0%), and the consumption of coffee (96.0%) and tobacco (78.0%) as toxic habits and acute heart attack as main complication. Conclusions: The achievement of the suitable therapeutic plan, knowledge on the disease, healthy feeding, the frequent practice of physical exercises and the appropriate lifestyle are fundamental to maintain the blood pressure controlled and avoid the emergence of complications.